Smartphone Distraction And Work Performance Among Gojek Drivers In Bekasi City: A Correlational Study - Ardian Firdaus Saputra; Yuarini Wahyu Pertiwi; Wahyu Aulizalsini Alurmei (Journal of Psychology and Social Sciences, 2026)
The proliferation of smartphone technology in gig economy settings has created a paradoxical dynamic for platform-based workers who simultaneously rely on and are potentially distracted by these devices. This study investigated the relationship between smartphone distraction and work performance among Gojek drivers in Bekasi City. Employing a quantitative correlational design, the study recruited 96 Gojek drivers through purposive sampling. Data were collected using the Smartphone Distraction Scale (SDS; Mascia et al., 2023) and the Employee Job Performance Scale (EJP; Na-Nan et al., 2018), and analyzed through Spearman’s rank-order correlation given the non-normal distribution of the data. The results indicated a statistically significant negative relationship between smartphone distraction and work performance (ρ = −0.288; p = 0.004), albeit with weak effect size. These findings suggest that higher levels of smartphone distraction are associated with lower work performance, though the relationship is moderated by the functional role of smartphones in ride-hailing work contexts. The study contributes to the growing literature on digital distraction in occupational settings and underscores the importance of examining contextual factors when assessing technology-related work performance outcomes   Penelitian ini mengkaji hubungan antara distraksi ponsel pintar dan performa kerja pada pengemudi Gojek di Kota Bekasi. Dengan menggunakan desain korelasional kuantitatif, sebanyak 96 pengemudi Gojek direkrut melalui teknik purposive sampling. Data dikumpulkan menggunakan Skala Distraksi Ponsel Pintar (SDS) dan Skala Kinerja Karyawan (EJP) dan dianalisis menggunakan korelasi Spearman’s rho karena distribusi data tidak normal. Hasil menunjukkan hubungan negatif yang signifikan antara distraksi ponsel pintar dan performa kerja (ρ = −0,288; p = 0,004) dengan kekuatan hubungan yang lemah. Temuan ini mengindikasikan bahwa tingkat distraksi ponsel pintar yang lebih tinggi berkaitan dengan performa kerja yang lebih rendah, meskipun hubungan tersebut dimoderasi oleh peran fungsional ponsel pintar dalam konteks pekerjaan berbasis platform.